"I Wouldn't Bring in Anything that Could Be Challenged": Educators as Moral Educators. (December 2019) - Walther, Carol S.; Wickens, Corrine M.; Koss, Melanie D.
Rooted in protectionist discourses, would-be censors regularly frame censorship and book challenges as defenses against portrayals of deviance and social ills. Such concerns often feed into social control of community values and moral panics around the degradation of children's presumed innate innocence. In this study, we investigated perceptions of public K-12 educators regarding the inclusion or exclusion of controversial materials in schools. We found that the "parent phone call" both served to define what constituted controversial materials and constrain educators' professional decision making. Although the rare teacher used parent phone calls as opportunities to educate parents about curriculum, the majority of educators avoided instructional practices that might elicit such a phone call, thus engaging in self-censorship and moral entrepreneurship as rule enforcers.